THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL CREATIVE PROBLEM SOLVING CAPACITY - Stevanovic, Ana (International Journal of Economic Practice and Policy, 2016)
In order to successfully operate and remain in contemporary turbulent marketplace, organizations need to foster their employees’ creativity, because it is a prerequisite of organizational innovation. As creativity is a precursor of innovation, and as innovation is an example of creative solutions implementation, there are numerous situations which require creative behavior of employees and that can be labeled as "problems". Therefore, creative problem solving turns out to be relevant in understanding of creativity. The aim of this paper is to offer an answer to the question - how transformational leadership influences the improvement of the capacity for creative problem solving within the organization. On the basis of the relevant literature, but also numerous practical examples of successful companies, we realized that transformational leaders foster a creative attitude of the employees and help them to build capacity for creative problem solving. Also, we realized that many studies have neglected the psychological conditions under which this exchange takes place. As creative problem solving requires extensive and strenuous cognitive processes, we assumed that the role of psychological safety is necessary because employees need to feel free during proposing new creative solutions.